Increased Weekly Mean PM2.5, and NO2 Are Associated With Increased Proportions of Lower Airway Granulocytes in Ontario Horses - Brankston, Gabrielle; Greer, Amy L.; Marshall, Quinn; Lang, Brittany; Moore, Kai; Hodgins, Douglas; Hennessey, John T. G.; Beeler-Marfisi, Janet (Frontiers in Veterinary Science, 2020)
Ambient pollution is associated with the development and exacerbation of human asthma, but whether air pollution exposure is associated with lower airway inflammation in horses has not been fully evaluated. The Air Quality Health Index (AQHI) is an online tool used by asthmatic Ontarians to modify their outdoor activity when ambient pollution is high. A single AQHI value, falling on a scale from one to ten+, is calculated from measurements of fine particulate matter (PM2.5), nitrogen dioxide (NO2), and ozone (O3). Increased AQHI values predict an increased risk for presenting to a health care provider for assessment of asthma exacerbation, with a time lag of zero to nine days after an increase. Whether ambient air pollution is a risk factor for identifying increased lower airway inflammatory cells on cytologic evaluation of bronchoalveolar lavage fluid (BALF) has not yet been explored. To investigate this relationship, case data including BALF cytology preparations from horses across southern Ontario, Canada, were retrieved from the Guelph Animal Health Laboratory’s archives. Spanning the years 2007 – 2017, 154 cases were identified within a 41- by 30-km area surrounding the cities of Guelph and Kitchener. In 78 of 154 cases, cytologic reevaluation identified increased proportions of one or a combination of BALF neutrophils (mean 5%, range 0-15%), eosinophils (mean 2%, range 0-31%) and mast cells (mean 4%, range 0-10%). To assess the effect of lagged pollutant and temperature exposures in these 78 cases, weekly mean values of AQHI, PM2.5, NO2, O3, and temperature were recorded for the four weeks prior to the date of the horse’s presentation for respiratory tract evaluation. The relationship between ambient exposures and increased proportions of lower airway granulocytes was evaluated using a case-crossover design. Single unit increases in two-, and three-week lagged weekly mean PM2.5 and NO2, were associated, respectively, with an 11% (p = 0.04, 95% confidence interval, CI, 1.01-1.22,), and 24% (p = 0.03, 95% CI 1.08 – 1.43) greater risk of identifying increased lower airway granulocytes. These findings suggest that exposure to increased ambient pollutants is associated with lower airway inflammation in Guelph and Kitchener area horses.